Futebol, ditadura e trabalho: uma análise das relações políticas e sociais no campo desportivo paraense (1964 – 1978) - MONTEIRO, Sinei Soares (Universidade Federal do Pará, 2013)
This dissertation will discuss the relevance of soccer in Brazilian society, especially in the state of Pará in the 20th century, more precisely in the context of a military dictatorship that reigned in Brazil back then (1964-1978). It is based on substantial documentation from Arthur Viana Library‘s archive, sports organizations‘ records, sports magazines, work contracts, lawsuits and statements, and also a huge bibliography covering that topic. This paper will help understand how social and political relationships were built in connection with local sports activities during the 20th century, highlighting negotiations and conflicts that took place in the construction process of the Mangueirão state soccer stadium, including the foundation and fortification of the Soccer Federation of Pará, and performs an analysis of work relationships established among the people daily involved with soccer in Pará.